Intensidade e uniformidades de distribuição de precipitações produzidas por um simulador de chuvas rotativo - Ferreira Valente, Osvaldo; Torres Loureiro, Blanor; Maffia de Oliveira, Laede; Carvalho Alves da Silva, Telmo (Revista Ceres, 2025)
This study was carried out at the Federal University of Vicosa to evaluate the operation of a rotating rainfall simulator similar to the model used at the University of Nebraska. Uniformity coeficients and precipitation rates were determined for several combinations of nozzles. These results may be useful in future rainfall simulator research applied to soil conservation, principally concerning small particle erosion.